The physical characteristics of preschool children and schoolchildren in relation to the type of nutrition in infancy - Hrušková, Martina; Ťoupalová, Lenka; Vašková, Iveta; Rejtharová, Denisa; Kobzová, Jarmila (Anthropologie, 2020)
We assessed the selected physical characteristics of 216 (108 boys and 108 girls) breastfed and 175 (84 boys and 91 girls) non-breastfed children aged 5, 9 and 14 years old. The measured characteristics were body height, body weight, selected circumferences (the right arm circumference, waist circumference, gluteal circumference and right thigh circumference) and skinfolds (the skinfold over the musculus triceps brachii, subscapular skinfold, suprailiacal skinfold and skinfold over the musculus quadriceps femoris). The Body Mass Index (BMI) and the sum of all four skinfolds were calculated as well. The results showed that the differences in mean values between breastfed and non-breastfed boys and girls are statistically insignificant (rated by Student's t-test and Mann–Whitney U test).
Keywords: Male; Child, Preschool; Body Weights and Measures; Child; Breast Feeding; tloušťka kožní řasy; dítě; tělesné váhy a míry; antropometrie; mužské pohlaví; kojení; Child Nutritional Physiological Phenomena; Anthropometry; předškolní dítě; lidé; ženské pohlaví; Humans; Body Mass Index; Skinfold Thickness; fyziologie výživy dětí; index tělesné hmotnosti; Female